River blockage and impulse wave evolution of the Baige landslide in October 2018: insights from coupled DEM-CFD analyses - Li, Dongyang (2023)
On 11 October 2018, the Baige landslide in Southwest China blocked the Jinsha River and induced waves amplifying the landslide-affected area significantly. Devastating flood damage was caused by the consequent dam breach. Such a complex sequence can lead to catastrophic consequences but has rarely been fully reproduced. This paper investigates the landslide-river interaction of the first Baige landslide based on coupled discrete element method (DEM) and computational fluid dynamics (CFD) analyses. To this end, the volume of fluid (VOF) and virtual sphere model are adopted to realise impacted river tracing and accurate terrain modelling. The damming process and impulse wave evolution of the first event are well represented. In addition, the simulated cumulative landslide spreading path, deposit geometry, maximum wave elevation and cumulative wave erosion area satisfactorily match the survey results. Our findings further indicate that the movement path and deposit morphology of the Baige landslide are mainly affected by local terrain, while the propagation of impulse waves is driven by the sliding mass and modulated by the riverbank and hydrodynamic conditions. In particular, we discussed the evolution patterns of impulse waves caused by river damming landslides, encompassing run-up on the opposite bank and quasi-3D propagation along the river direction. This research provides a valuable guide for the practical simulation of river blockage and impulse wave evolution and supports the mitigation of landslide disasters in mountainous areas.